From 'moule' to 'modulation': logics of Deleuzean 'control' in recent reforms to French labour law - Lane, Jeremy F. (Taylor & Francis, 2018)
In his influential ‘Postscriptum sur les sociétés de contrôle’ (1990), Gilles Deleuze argues that one defining characteristic of contemporary ‘societies of control’ is that salaried labour functions no longer as a ‘moule’, defining workers’ identities once and for all, but rather as an open-ended process of ‘modulation’, in which workers must constantly adapt their identities and aptitudes. This article argues that Deleuze’s distinction between ‘moule’ and ‘modulation’ offers a highly productive lens through which to analyse a representative sample of changes to the organisation and legal regulation of work in France from the 1990s to the present: the MEDEF’s embrace of the compétences agenda in the late 1990s, the 2013 Loi sur la sécurisation de l’emploi, the loi El Khomri of 2016, and Macron’s five ordonnances in 2017. The article places these measures in a much broader domain of debates that emerged in the 2000s about the best way to reform France’s welfare system in the light of the increase in precarious and atypical forms of labour contract. The intensity of these debates points to a shared realisation that the disciplinary forms of the post-war Fordist compromise are now definitively in crisis. What remains to be seen is whether this crisis will simply herald the wholesale neo-liberal deregulation of work and welfare or whether this shift from ‘moule’ to ‘modulation’ may yet provide the bases of a new compromise between capital and labour, a compromise better adapted to our ‘societies of control’.